Antirollover Experimental Method for a Liquid Tank Semitrailer - Miao Yu; Shiwu Li; Wencai Sun; Xue Wen; Dongye Lv (Journal of Advanced Transportation)
The liquid tank semitrailer has higher centroid and poor stability, and the vehicle is prone to rollover when turning or changing lanes at high speed. Thus, many companies have developed active antirollover systems in recent years. But the systems’ antirollover capabilities are different. However, there are no specific test conditions and test standards for antirollover systems. Taking this as a starting point, first, an automotive intelligent security cloud terminal and a multiaxis sensor are selected for the test data acquisition, and a remote data acquisition system based on a mobile signal is established. Second, a vehicle road test scheme with a free choice of route is designed. Set the rollover trigger conditions, obtain the test data through the database, and classify the data into dangerous scenarios. Third, the typical scenarios with rollover risk are obtained by data fitting. Finally, the typical antirollover system test conditions of the liquid tank semitrailer are obtained by optimizing and analysing the typical scenarios through the simulation software. The results show that the J-steering test with a turning radius of 45 m in both clockwise and counterclockwise directions can be used as an accurate typical test condition of the antirollover system of liquid tank semitrailers.